2020
DOI: 10.1186/s12936-020-03337-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of imported Plasmodium ovale spp. and Plasmodium malariae in Hubei Province, China, 2014–2018

Abstract: Background: There have been an increasing number of imported cases of malaria in Hubei Province in recent years. In particular, the number of cases of Plasmodium ovale spp. and Plasmodium malariae significantly increased, which resulted in increased risks during the malaria elimination phase. The purpose of this study was to acquire a better understanding of the epidemiological characteristics of P. ovale spp. and P. malariae imported to Hubei Province, China, so as to improve case management. Methods: Data on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…by Sutherland et al 25 , and 2020. The majority of included studies (14/36, 38.9%) were conducted in African countries (1 in Angola 9 , 1 in Equatorial Guinea 26 , 2 in Ethiopia 5 , 8 , 2 in Gabon 43 , 51 , 1 in Ghana 15 , 1 in Kenya 46 , 1 in Namibia 44 , 2 in the Republic of Congo/Congo 26 , 42 , 2 in Senegal 6 , 7 and 1 in Uganda 26 ), Asian countries (9 in China 12 , 14 , 32 , 35 , 39 , 49 , 50 , 52 , 53 , 2 in India 10 , 11 , 1 in Bangladesh 41 , 1 in Myanmar 12 and 1 in Thailand 13 ), Europe (3 in Italy 29 31 , 2 in France 23 , 45 , 2 in Spain 47 , 48 , 2 in the United Kingdom 25 , 34 and 1 in Germany 40 ) and Northern America (1 in Canada 28 ). Most of the included studies 23 , 25 , 28 , 30 – 32 , 34 , 35 , 39 , 40 , 45 , 47 – 50 , 52 , 53 (19/36, 52.8%) reported indigenous cases of malaria caused by P. ovale curtisi or P. ovale wallikeri , and the remaining studies (17/36, 47.2%) reported imported cases.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…by Sutherland et al 25 , and 2020. The majority of included studies (14/36, 38.9%) were conducted in African countries (1 in Angola 9 , 1 in Equatorial Guinea 26 , 2 in Ethiopia 5 , 8 , 2 in Gabon 43 , 51 , 1 in Ghana 15 , 1 in Kenya 46 , 1 in Namibia 44 , 2 in the Republic of Congo/Congo 26 , 42 , 2 in Senegal 6 , 7 and 1 in Uganda 26 ), Asian countries (9 in China 12 , 14 , 32 , 35 , 39 , 49 , 50 , 52 , 53 , 2 in India 10 , 11 , 1 in Bangladesh 41 , 1 in Myanmar 12 and 1 in Thailand 13 ), Europe (3 in Italy 29 31 , 2 in France 23 , 45 , 2 in Spain 47 , 48 , 2 in the United Kingdom 25 , 34 and 1 in Germany 40 ) and Northern America (1 in Canada 28 ). Most of the included studies 23 , 25 , 28 , 30 – 32 , 34 , 35 , 39 , 40 , 45 , 47 – 50 , 52 , 53 (19/36, 52.8%) reported indigenous cases of malaria caused by P. ovale curtisi or P. ovale wallikeri , and the remaining studies (17/36, 47.2%) reported imported cases.…”
Section: Resultsmentioning
confidence: 99%
“…The latency period in each study was calculated from the period in days between the last date in the malaria-endemic country and presentation to the hospital in the non-endemic country. Eight studies 30 , 32 , 34 , 40 , 47 , 48 , 52 , 53 reported the mean latency period (days) of P. ovale spp. and were included in the analysis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations